Pan American first test flight: transatlantic, 1937 [part 1] - Pan American World Airways, Inc. (1937)
Includes photographs and news clippings. Some materials in this folder were not scanned due to copyright concerns, but are available for viewing at the University of Miami Libraries Special Collections. This item was digitized as part of the "Digitizing the 'World's Most Experienced Airline'" project, supported by a grant from the Council on Library and Information Resources (CLIR). The grant program is made possible by funding from The Andrew W. Mellon Foundation.